Resonant Damping of Propagating Kink Waves in Non-stationary, Longitudinally Stratified, and Expanding Solar Waveguides - Ruderman, Michael S.; Shukhobodskaya, Daria; Shukhobodskiy, Alexandr A. (Frontiers in Astronomy and Space Sciences, 2019)
Propagating kink waves have been observed in many magnetic waveguides in the solar atmosphere, like coronal magnetic loops, spicules, and fine structures of prominences. There are also observational evidences that these waves are damped. At present resonant absorption is considered as the most likely candidate for explaining this damping. First the attenuation of propagating kink waves due to resonant absorption was studied using the simplest model with a straight magnetic tube and the density only varying in the radial direction. Later a more advanced model with the density also varying along the tube was used. It was shown that the variation of the wave amplitude along the tube is determined by the combined effect of resonant damping and the longitudinal density variation. In our article we extend the analysis of resonant damping of propagating kink waves to take into account the magnetic loop expansion. We also consider non-stationary magnetic tubes to model, for example, cooling coronal loops. In particular, we found that cooling enhances the wave amplitude and the loop expansion makes this effect more pronounced.